Quantum field theory : A twentieth century profile (New Delhi: Hindustan Book Agency, 2000)
This volume reflects the huge and multi-dimensional impact of quantum field theory on the evolution of physics in the 20th century. Dr. Asoke Mitra, editor for the volume and former student and colleague of Freeman Dyson, gathers here a selection of articles in the areas where the impact of QFT has been especially pronounced: from particle physics to string theory and extending to facets of astrophysics and the physics of condensed matter.
Includes bibliographical references
Keywords: Quantum Field Theory; Physics